The Influence of Liquidity, Leverage, Company Size and Profitability on Financial Distress - Andi Runis; Dedy Samsul Arifin; Arifuddin Masud; Ummy Kalsum (International Journal of Business and Social Science Research, 2021)
This study aims to empirically examine the factors that influence Financial Distress in Property and Real Estate Companies. This study was tested with four independent variables, namely Liquidity (Current Ratio), Leverage (Debt Equity Ratio), Firm Size (ln of Total Assets), and Profitability (Return on Assets) using purposive sampling technique the authors chose seventeen companies as samples. This study uses panel data analysis obtained from financial reports and Annual Reports for 5 years. This study uses secondary data with the help of the Eviews 9 application. The results found that the Leverage Variable (Debt Equity Ratio) has a positive and significant influence on Financial Distress while Liquidity (Current Ratio), Company Size (ln of Total Assets), and Profitability Variables (Return). on Assets) has a negative and significant effect on Financial Distress.